Understanding superiority, noninferiority, and equivalence for clinical trials - Kamal Kishore (Indian Dermatology Online Journal, 2020)
Randomized control trialsare the gold standard for testing the efficacy of new interventions. Historically, superiority trials were methods of choice as reference (standard) interventions were not established for many disease conditions. However currently, reference interventions are available for most of adverse conditions. Despite this, many investigators are using superiority trials in comparison to more suitable noninferiority and equivalence trials. The application of noninferiority and equivalence trials is on the rise, but by and large, these trials are poorly understood, ill-conceived, inappropriately analyzed, and reported and misinterpreted.